Locomotor Behavior of Chickens Anticipating Incline Walking - LeBlanc, Chantal; Tobalske, Bret; Szkotnicki, Bill; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2018)
Keel bone damage (KBD) is prevalent in hens raised for egg production, and ramps between different tiers in aviaries have potential to reduce the frequency of falls resulting in KBD. Effective use of ramps requires modulation of locomotion in anticipation of the incline. Inadequate adaptive locomotion may be one explanation why domestic layer hens (Gallus gallus domesticus) exhibit high rates of KBD. To improve understanding of the capacity of hens to modulate their locomotion in anticipation of climbing, we measured the effects of incline angle upon the mechanics of the preparatory step prior to ascending a ramp. Because the energetic challenge of climbing increases with slope, we predicted that as angle of incline increased, birds during foot contact with the ground before starting to climb would increase their peak force and duration of contact and reduce variation in center of pressure under their foot. We tested 20 female domestic chickens on ramp inclines at slopes of +0 º, +40 º and +70º when birds were 17, 21, 26, 31, and 36 weeks of age. There were significantly higher vertical peak ground reaction forces in preparation at the steepest slope, and ground-contact time increased significantly with each increase in ramp angle. Effects upon variation in center of pressure were not apparent; likewise, effects of limb length, age, body mass were not significant. Our results reveal that domestic chickens are capable of modulating their locomotion in response to incline angle.